2016
DOI: 10.1155/2016/9302692
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Patterns of Bacterial Isolates from Pus Samples in a Tertiary Care Hospital of Punjab, India

Abstract: We determined the prevalence and antibiotic susceptibilities patterns of bacterial isolates from pus samples collected from patients in a tertiary care hospital of Punjab, India. E. coli was the most prevalent pathogen (51.2%) followed by Staphylococcus aureus (21%), Klebsiella pneumoniae (11.6%), Pseudomonas aeruginosa (5.8%), Citrobacter spp. (3.5%), Acinetobacter baumannii (2.3%), Proteus mirabilis (2.3%), and Streptococcus spp. (2.3%). E. coli, K. pneumoniae, A. baumannii, and Citrobacter isolates were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
52
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 17 publications
28
52
5
Order By: Relevance
“…In this study, the pus culture positivity rate in clinically suspected cases was 59.92% which is comparable to the previous reports of Rai et al, (2017) (59%) and Trojan et al, (2016) (60.1%). The male: female distribution of pus isolates was found to be 1.30:1 while the study of Rao et al, 2014 showed 1.43:1 ratio.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the pus culture positivity rate in clinically suspected cases was 59.92% which is comparable to the previous reports of Rai et al, (2017) (59%) and Trojan et al, (2016) (60.1%). The male: female distribution of pus isolates was found to be 1.30:1 while the study of Rao et al, 2014 showed 1.43:1 ratio.…”
Section: Resultssupporting
confidence: 89%
“…Since these infections are associated with high morbidity prompt antibiotic therapy is mandatory. An increase incidence of multidrug resistant Gram negative bacteria and Methicillin resistant Staphylococcus aureus is frequently isolated from pyogenic infections under hospital settings (Muluye et al, 2014;Trojan et al, 2016). The emergence of antibiotic resistant pathogens poses a grave threat to the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results, with a subtle difference, were found elsewhere too [30] another study in Egypt [31]. Our Citrobacter youngae, showed resistance to almost all the antibiotics tested are in concomitant with some recent studies [38] [39] [40]. The Pseudomonas aeruginosa was resistance to Piperacillin, Ceftazidime, Ampicillin, Azteroname, Augmentin and Cephalothin [31] [36].…”
Section: Discussionsupporting
confidence: 91%
“…Majority of mastitis causing pathogens are normally found intermediate resistant to the antimicrobials used for treatment, but in past two decades few studies have signposted an augmented resistance of S. aureus and CNS to β-lactam antibiotics (Trojan et al 2016). In a view of this, the emergence of methicillin resistance among Staphylococcus spp.…”
Section: Issn: 2320-5407mentioning
confidence: 99%